Optical diffraction by ordered 2D arrays of silica microspheres. (March 2017) - Shcherbakov, A.A.; Shavdina, O.; Tishchenko, A.V.; Veillas, C.; Verrier, I.; Dellea, O.; Jourlin, Y.
Abstract: The article presents experimental and theoretical studies of angular dependent diffraction properties of 2D monolayer arrays of silica microspheres. High-quality large area defect-free monolayers of 1 μm diameter silica microspheres were deposited by the Langmuir-Blodgett technique under an accurate optical control. Measured angular dependencies of zeroth and one of the first order diffraction efficiencies produced by deposited samples were simulated by the rigorous Generalized Source Method taking into account particle size dispersion and lattice nonideality. Abstract : Highlights: High quality silica microsphere monolayer was fabricated. Accurate measurements of diffraction efficiency angular dependencies. Rigorous diffraction simulation of both ideal hexagonal and realistic microsphere arrangements. Qualitative rationalization of the obtained results and the observed differences between the experiment and the theory.